Dialogias no cronotopo pandêmico: sentidos emergentes em narrativas sobre o ensino-aprendizagem em uma escola pública do Piauí - Queiroz, Marília Mesquita (2025)
In the chronotope of the covid-19 pandemic, institutions across various spheres of human activity were compelled to self-organize in response to the unforeseen circumstances faced during this period. In the field of education, these rearrangements have been documented through diverse lenses, contributing to the understanding of how school systems adapted in different contexts. This study, grounded in categorical narrative research (Breton, 2023; Clandinin et al., 2016; Paiva, 2019; Reis, 2023), analyzes reports from the book “Sozinho na minha torre”: representações discentes sobre o ensino remoto no Piauí, written in 2023 by high school students from a federal institution in Piauí. The objective is to examine the meanings these students attribute to remote teaching and learning, particularly in relation to the English language. Based on the understanding of education as a complex phenomenon (Davis and Sumara, 2006; Freire, 2011; Freire, 2013; Morin, 1995; Morin, 2021), we reflect on the multidimensionality inherent to the school system and on the interactive and inter-retroactive relationships between learning and teaching. Analytical categories and concepts include dialogism, meaning (Bakhtin, 2017 [1979]; Volóchinov, 2018; Vygotsky, 2007), chronotope (Bakhtin, 2018 [1975]; Bemong, 2015), autonomy (Morin, 2021; Paiva, 2005), and emotion (Aragão, 2008; 2011; Maturana, 2001; Maturana e Varela, 1998), which emerge consistently in the students’ narratives. Considering the shift from physical to virtual learning environments, the study also addresses digital literacy, with support from Coscarelli (2016), Lankshear and Knobel (2006), Rojo and Moura (2019), Santaella (2010), Soares (2002, 2009), and Street (2013, 2014). Besides serving as a historical record of the educational experience during the pandemic, the research highlights the value of amplifying student voices, reinforcing their legitimacy and capacity to inform systemic improvements. As an applied study, it further explores non-linearity, complexity, and possibilities in language teaching and learning, building on Larsen-Freeman and Cameron (2008) and Paiva (2010, 2014), among others. The findings indicate that remote teaching was often perceived as having limited relevance for learning, prompting some students to engage in autonomous learning practices, both generally and specifically in the English subject. The home, as the new learning space, was reinterpreted with varied meanings: confinement, confusion, leisure, overload, and overcrowding. Emotional and psychological impacts – such as fear, anxiety, and difficulties in concentration and social interaction upon returning to in-person classes – were also frequently reported.